A poesia antiescravista de Trajano Galvão de Carvalho: uma leitura acerca da representação do negro em Sertanejas (1898) - Carvalho, Iariny de Fátima Uchôa (2023)
The Maranhão poet Trajano Galvão de Carvalho (1830-1864), even though he is pointed out for the anti-slavery character of his lyrical poetry, has a reduced critical fortune that can be summarized in repetitions of works already developed by authors such as Silvio Romero or Antônio Henriques Leal. With this in mind, the present study proposes to situate the poet's work in the panorama of Brazilian romantic literature from the author's bibliographic review in order to contribute to the reinsertion of his poetry in literary studies. Our study focuses on the thematic analysis of the poet's authorial poems – published in the posthumous volume Sertanejas (1898) – considering the pioneering spirit of Trajano Galvão in the thematic anti-slavery approach in Brazilian lyric poetry. The alignment of Trajano Galvão de Carvalho with the lyrical production of Brazil until then is notorious, in addition to already presenting the traces of the pioneering spirit that would consecrate his work. In addition, the poet presents himself not only as a precursor of the abolitionist theme in Brazil, but also as one of the first to portray, in Brazilian poetry, the subjectivity of the enslaved black subject, annulled by the country's slave system.